Climate change perceptions among Australian non-frequent flyers. Issue 1 (2nd January 2017) - Reis, Arianne C.; Higham, James E. S.
ABSTRACT: Growing acceptance and concern about anthropogenic climate change is beginning to influence tourists' travel practices, with a hardening of attitudes towards long-haul aviation now evident in a number of key European outbound tourism markets. This raises timely questions as to whether or not the need for urgent climate action is influencing air travel decisions in other markets. This paper investigates climate concerns and air travel practices in the Australian outbound tourism market. Specifically, we set out to examine whether or not climate concerns may be influencing Australian non-frequent travellers to consider distance as a factor in their air travel destination decision-making, with a particular focus on New Zealand as a destination. Reflecting previous studies, the results indicate widespread concern about climate change combined with an unwillingness to change established air travel behaviours. However, in contrast to previous research, participants in this study did not show an overt and passive 'attitude-behaviour gap' based on denial and guilt, but a more conscious reasoning that led to scepticism towards their individual ability to enact change while operating in a system that is not really geared to make this change possible.